2015
DOI: 10.3109/13880209.2015.1005756
|View full text |Cite
|
Sign up to set email alerts
|

Detection of plant-based adulterants in turmeric powder using DNA barcoding

Abstract: Context: In its powdered form, turmeric [Curcuma longa L. (Zingiberaceae)], a spice of medical importance, is often adulterated lowering its quality. Objective: The study sought to detect plant-based adulterants in traded turmeric powder using DNA barcoding. Materials and methods: Accessions of Curcuma longa L., Curcuma zedoaria Rosc. (Zingiberaceae), and cassava starch served as reference samples. Three barcoding loci, namely ITS, rbcL, and matK, were used for PCR amplification of the reference samples and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 32 publications
4
31
0
Order By: Relevance
“…2,9,12,16,33,34) However, little is known about the relationship of genetic and chemical differences by using integrated approach. In this study, we found a low correlation (r=0.1721, p=0.047) between genetic distance and HPLC distance using the Mantel test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,9,12,16,33,34) However, little is known about the relationship of genetic and chemical differences by using integrated approach. In this study, we found a low correlation (r=0.1721, p=0.047) between genetic distance and HPLC distance using the Mantel test.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 2) showed that the primer pair 390F/1326R did not work for matK gene amplification in turmeric. In contrast, we found that this primer pair produced PCR products if additional PCR cycles (45) were completed ( Table 1).…”
Section: Identifying Commercial Samples Using Rbcl and Matk Sequencesmentioning
confidence: 99%
“…As an example, DNA barcoding was used to characterize the bean germplasm ( Phaseolus vulgaris L.) and was found able to distinguish among different haplotypes of bean accessions from the Mesoamerican and Andean areas [ 57 ]. Similarly, the DNA barcoding approach was adopted to assess the origin and quality of spices [ 44 , 58 ], herbal products [ 59 , 60 ], and naturally processed plant products such as multiflower honey [ 61 ]. Other studies investigated the ability of DNA barcoding in discerning toxic plants from edible species: cultivated species of the genera Solanum and Prunus were successfully distinguished from their toxic congenerics [ 62 ] and from some frequent plant species misidentifications that cause poisoning in human [ 63 ].…”
Section: Dna Barcoding: a Universal Approach For Food Characterizamentioning
confidence: 99%
“…Therefore, the presence of other Curcuma species, such as C. zedoaria and C. xanthorhhiza, has been detected in turmeric powder sold in India [9]. Some analytical methods have been developed for authenticating medicinal plants, including fingerprint analysis using High-Performance Liquid Chromatography-Diode Array Detector (HPLC-DAD) combined with chemometrics [7], metabolomics technique using Proton Nuclear Magnetic Resonance (H-NMR) combined with multivariate analysis [10], and DNA based approach using DNA Barcoding [9], Random Amplified Polymorphic DNA (RAPD) [11], and Sequence Characterized Amplified Region (SCAR) [12]. The main disadvantage of these methods is that several steps are needed for sample preparation, making the process slow and costly.…”
Section: Introductionmentioning
confidence: 99%